A Tuberculose no Estado da Paraíba, Brasil: análise da incidência, proporção de cura e tempo de tratamento - Oliveira, Bueno Callou Bernardo de (2020)
Although from 2007 to 2016 the incidence coefficient of tuberculosis in Brazil showed an average annual drop percentage of 1.7%, it is particularly worrying the upward trend in the notification of new cases in the years that followed. Regarding the success of the treatment, the country presented in 2018 a cure rate of 71.9% of the new cases of pulmonary tuberculosis with laboratory confirmation, still far from the minimum percentage of 85% recommended by the World Health Organization, highlighting that units from the Federation, specifically Paraíba and the Federal District, showed cure rates for tuberculosis below 60%. This study aimed to assess the burden and impact of tuberculosis in the state of Paraíba in the last decade. This is an ecological study composed of three evaluative components of new cases of tuberculosis, drug-resistant tuberculosis, of tuberculosis with Special Scheme, and of nontuberculous mycobacterioses notified in the state of Paraíba in the period from 2010 to 2019, being the first component of analysis of the time trend of the incidence coefficients, the second component of comparative analysis of the proportion of cure, proceeding if the isolated analysis of the temporal trend of the cure rate of new cases of tuberculosis with laboratory confirmation, and the third component of comparative analysis of treatment time. In the analysis of the temporal trend of the incidence of cases, it was found that all the coefficients showed a pattern of stability in the period observed, with slight annual variations. There was a statistically significant difference in the comparative analysis of cure percentages (p <0.001) and in the comparative analysis of treatment time (p <0.001). In decreasing order, the cure rate for new cases of tuberculosis was 78.6%, for new cases of tuberculosis with Special Scheme, 66.9%, for new cases of drug-resistant tuberculosis, 52.8% and the number of new cases of nontuberculous mycobacteriosis was 52.4%, a result that is ecologically associated with the treatment time of the cases, so that in an increasing order, the new cases of tuberculosis presented an average of 6.72 months of treatment, those with tuberculosis with a Special Scheme of 10.51 months, those with nontuberculous mycobacterioses of 14.36 months and those with drug-resistant tuberculosis of 14.95 months. The analysis of the temporal trend applied to the second component showed that the cases with ignored closure and transfer have contributed predominantly to the decrease in the proportion of tuberculosis cure in the state of Paraíba in recent years. It is concluded with the study that the burden of tuberculosis in the state of Paraíba no longer shows decreasing annual variations when analyzing the recent historical series, and that the expressive number of new cases of tuberculosis with ignored closure or by transfer constitutes fearful gap in disease surveillance, capable of skewing the information-decision-action process. Finally, it was possible to observe by ecological association that as the treatment time of the cases increases, the percentage of cure decreases dramatically.